Digital Governance and Healthcare Logistics: Driving Efficiency with eLMIS in Nepal - Yadav, Mahesh Kumar (Patan Prospective Journal, 2024)
An Electronics Logistics Management Information System eLMIS in revolutionizing healthcare supply chains in Nepal. By leveraging real-time data analytics and distribution of health commodities across the nation’s diverse topography. The study evaluates eLMIS's implementation, highlighting its benefits in improving decision-making, inventory management, and supply chain visibility. Key findings, challenges, and strategic recommendations are discussed to optimize eLMIS operations, ultimately aiming to enhance healthcare delivery and support e-government initiatives in Nepal.